Analisis Perancangan Website Deflash Laundry Menggunakan HTML dan CSS Untuk Pengembangan Pemasaran - Rahma Yuni Anti; Aidatul Salmi; Olivia Dwiputri (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
The creation of a website-based information system is used for the efficiency and effectiveness of the MSME actors studied. In creating the Deflash Laundry Website, a system design using the Waterfall method was used which was deemed effective and the programming languages used were HTML and CSS. Website implementation is used via the tooplate.com template which is then edited to be relevant to the MSMEs studied. The results of the Deflash Laundry Website design are very practical, making it easier for business owners to distribute them.